Playing surface and UK professional rugby union injury risk. Issue 21 (2nd November 2018) - Ranson, Craig; George, Jonathan; Rafferty, James; Miles, John; Moore, Isabel
ABSTRACT: Artificial rugby union playing surface installation is increasing. This prospective cohort study aimed to examine the effect of playing surface on match injury types within 157 players of two UK professional rugby union clubs playing 209 matches (96 on artificial surfaces and 113 on grass) over three seasons. There was no difference in overall injury risk between the two playing surfaces with injury incidence on artificial 80.2 (CI 69.9–91.7) and on grass 81.9 per 1000 match-hours (CI 72.2–92.5), with an incidence rate ratio (RR) of 0.98 (CI 0.82–1.17). There was a higher rate of concussion (RR 0.52, CI 0.34 – 0.78) and chest injuries on grass (RR 0.26 CI 0.07, 0.95), and a higher rate of thigh haematoma (RR 2.25, CI 1.05–4.82) foot injuries (RR 4.12, CI 1.10, 15.40) and injury to players being tackled (RR 1.46, CI 1.00, 2.15) on artificial. Whilst there was no higher injury risk for matches played on artificial versus natural grass surfaces, the higher incidence of concussion and chest injury on grass, and the higher rate of foot injuries on artificial surfaces may be related to tackle and footwear-to-surface interface factors.